2019
DOI: 10.3390/su11133513
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Land-Use Change on Habitat Quality during 1985–2015 in the Taihu Lake Basin

Abstract: Habitat quality (HQ) is of great significance to regional sustainable development, which is a key link for regional ecological security and human welfare. Assessing the temporal and spatial evolution of HQ caused by land-use change could provide a scientific basis for regional ecological protection and land management. Here, based on the ArcGIS platform and the InVEST model, this study quantified the spatial and temporal evolutions of land use, landscape patterns, and HQ from 1985 to 2015, in Taihu Lake Basin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 81 publications
4
63
0
3
Order By: Relevance
“…(1) At the patch-class level, the landscape pattern evolution characteristics of industrial rural areas in Southern Jiangsu were that construction land had continuously encroached on green and cultivated land in all four study areas, exhibiting trends of expansion, centralization and the continuous consolidation of small patches into large patches during evolution and ultimately replacing cultivated land as the dominant landscape category. The result was in accordance with those in the studies of Yang, Sun et al, Ma et al, Xu et al and Chuai et al [31][32][33][34][35]. The reasons might be as follows: (1) Relevant studies showed that under the background of rapid socio-economic development, urban master planning is constantly updated, and relevant policies and regulations constantly promote human beings to expand the scope of urban built-up areas through deforestation, farmland reclamation and civil construction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…(1) At the patch-class level, the landscape pattern evolution characteristics of industrial rural areas in Southern Jiangsu were that construction land had continuously encroached on green and cultivated land in all four study areas, exhibiting trends of expansion, centralization and the continuous consolidation of small patches into large patches during evolution and ultimately replacing cultivated land as the dominant landscape category. The result was in accordance with those in the studies of Yang, Sun et al, Ma et al, Xu et al and Chuai et al [31][32][33][34][35]. The reasons might be as follows: (1) Relevant studies showed that under the background of rapid socio-economic development, urban master planning is constantly updated, and relevant policies and regulations constantly promote human beings to expand the scope of urban built-up areas through deforestation, farmland reclamation and civil construction.…”
Section: Discussionsupporting
confidence: 92%
“…Among the four study areas, Kunshan exhibited the most significant landscape pattern evolution characteristics. This result was also in accordance with the results of the studies by Yang, Sun et al, Ma et al, Xu et al and Chuai et al [31][32][33][34][35]. The reason for the results might be as follows: (1) The gradual improvement of a traffic network would cause disorderly cutting of the original patch landscape, which seriously affects the circulation of the ecological function of the regional landscape.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Xu et al [37] included nine different threats in their study of impacts of land-use change on habitat quality in the Taihu Lake Basin. Additional to the typical urban threats considered in our study, they also included, for instance, industrial and mining land and paddy fields as threats to habitat quality.…”
Section: The Consideration Of Additional Lulc Class or Other Data Soumentioning
confidence: 99%
“…In recent years, the ecosystem is undergoing increasing pressures and degeneration owing to climate change, urban sprawl, and human activities [1][2][3][4]. The environmental problems following those pressures, such as global warming [5], soil erosion [6], desertification [7], environment pollution [8], and loss of biodiversity [9], have changed the ecosystem structure and process, decreased the ecosystem service value, and posed great threats to region sustainable development. Ecological vulnerability is regarded as a core issue in sustainability science [10], and it is an inherent property of an ecosystem.…”
Section: Introductionmentioning
confidence: 99%